HUBUNGAN TINGKAT PENGETAHUAN TENTANG PESTISIDA DENGAN PRAKTEK PENGGUNAAN ALAT PELINDUNG DIRI PADA PETANI KENTANG - Joko Malis Sunarno; Dwi Atin Faidah (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2018)
Controlling of chemical pesticide application represent the way of most practical, efficient and economic in overcoming pest. Usage of pesticide can make farmer contamination directly so that result poisoned. Usage of personal protective equipment (PPE) in pesticide application is importance to prevent incidence of chronic health diseases and acute. Practice of PPE influenced by knowledge level about pesticide. The aim of this research was to know relation between knowledge about pesticide with practice of PPE by potato farmer in Kepakisan Village Subdistrict of Batur, Banjarnegara. This research is observasional study with cross sectional design. The population are all of potato farmer in Kepakisan with samples taken by counted 76 responder. Sampel is conducted by simple random sampling. Data collecting was conducted with interview by quesionair to express characteristic data, knowledge level and practice of PPE. Data was analyzed by univariat with percentage of frequency distribution of variable. While bivariate analysis was used by correlation test to know relation between knowledge level of farmer with practice of PPE. Result of research showed that characteristic of most potato farmer reside in age 40-45 year group, men gender, and working time about more than 5 years old, alumna of elementary school or equal, and have less than minimum of district salary. Most farmer have score 5-10 poin of knowledge, most usage of PPE of potato farmer are complete (more than or equal to 5 used) that is equal to 75 %. There is significantly relation between knowledge level of farmer about pesticide with practice of PPE in Kepakisan. Socialization/ counselling concerning usage of pesticide and practice of PPE is expected in course of good management about pesticide which start from preparation phase, application and dismissal of pesticide remains to increase knowledge of farmer.